Waithood Phenomenon In Maqāṣid Al-Syarī‘ah Perspective: Implications for Contemporary Islamic Family Law - Munawar Munawar; Dede Permana (Nuris Journal of Education and Islamic Studies, 2026)
The phenomenon of waithood, which delays marriage for a long time due to social, economic, educational, and value-changing factors, has become a new reality in contemporary Muslim society. This phenomenon not only impacts social structures but also raises issues in Islamic family law, such as the increasing age of marriage, gender relations, family stability, and the potential for deviant behavior from sharia norms. This article aims to analyze the phenomenon of waithood from the perspective of maqāṣid al-syarī‘ah and its implications for the reform of contemporary Islamic family law. This study uses a qualitative approach with library research methods, analyzing classical and contemporary literature on maqāṣid al-syarī‘ah, family sociology, and Islamic family law regulations in various Muslim countries. The results of the study indicate that the phenomenon of waithood is closely related to the objectives of sharia, particularly in safeguarding religion (ḥifẓ al-dīn), soul (ḥifẓ al-nafs), reason (ḥifẓ al-‘aql), descendants (ḥifẓ al-nasl), and property (ḥifẓ al-māl). From a maqāṣid perspective, postponing marriage is justifiable as long as it aims to realize benefits and prevent harm, such as mental, economic, and social readiness. However, if waithood has the potential to undermine the objectives of sharia, normative intervention is needed through family law policies that are more adaptive, contextual, and responsive to social realities. This article emphasizes the importance of the maqāṣid al-shari‘ah approach as an ethical and normative foundation in formulating Islamic family law that is relevant to the challenges of modern society.